Influence of space-time heterogeneity of water consumption conditions on the parameters of a water supply system = Wpływ czasoprzestrzennej niejednorodności warunków poboru wody na parametry systemu wodociągowego - Ogiołda, Ewa; Nowogoński, Ireneusz; Babiuch, Maciej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The work presents the results of the analysis of an existing water supply system. It contains a description of the analysed area in which the analysed system was located, as well as its parameters regarding water intakes and transport of water with pumps, the length and diameter of pipes, and a complication of the materials used to construct the network.
Keywords: water consumption; irregularity; water supply network; hydraulic parameters; zużycie wody; nierównomierność; sieć wodociągowa; parametry hydrauliczne